WEBVTT
00:00:01.120 --> 00:00:06.160
Express cos cubed π in terms of the cosines of multiples of π.
00:00:07.280 --> 00:00:14.640
In this question, we want to find an expression for the cos cubed of π in terms of cosines of multiples of our angle π.
00:00:15.680 --> 00:00:21.280
The easiest way to answer this question will be to use De Moivreβs theorem.
00:00:22.040 --> 00:00:39.280
One version of De Moivreβs theorem tells us for any integer value of π and a real number π, cos π plus π sin π all raised to the πth power will be equal to cos ππ plus π sin ππ.
00:00:40.320 --> 00:00:52.720
If we wanted to use this to answer our question, we would need to choose our value of π equal to three, so cos cubed π appears in our expression.
00:00:53.600 --> 00:01:01.040
However, if we did this, when we distribute over our parentheses, we would end up with terms involving sin π.
00:01:02.080 --> 00:01:11.960
And the question only wants us to use terms involving cos π, so weβre going to need to use an extra result.
00:01:13.160 --> 00:01:27.840
If we set π§ to be the expression inside of our parentheses in De Moivreβs theorem, then De Moivreβs theorem tells us π§ to the πth power is equal to cos ππ plus π sin ππ.
00:01:28.680 --> 00:01:33.960
We can then use this to get two very useful results.
00:01:34.880 --> 00:01:48.320
π§ to the πth power plus one over π§ to the πth power is equal to two cos of ππ, and π§ to the πth power minus one over π§ to the πth power is two π sin of ππ.
00:01:49.360 --> 00:02:02.040
And we can prove these results by remembering De Moivreβs theorem works for any integer value of π and one over π§ to the πth power is equal π§ to the power of negative π.
00:02:02.240 --> 00:02:08.840
These two results are really useful and are worth committing to memory.
00:02:10.000 --> 00:02:19.640
We want to use these to find an expression for cos cubed of π, so weβre going to use the expression involving cosine.
00:02:20.440 --> 00:02:28.400
And weβll start by setting our value of π equal to one because we want to find an expression for cos cubed of just π.
00:02:29.480 --> 00:02:36.760
So by setting π equal to one, we get two cos of π will be equal to π§ plus one over π§.
00:02:37.640 --> 00:02:48.800
Next, we want an expression for cos cubed of π, so weβre going to need to cube both sides of our equation, and we could simplify both sides separately.
00:02:49.760 --> 00:02:54.480
On the left-hand side of our equation, we need to cube each of the factors separately.
00:02:55.080 --> 00:03:00.480
This gives us two cubed, which is eight multiplied by cos cubed of π.
00:03:01.360 --> 00:03:07.880
And on the right-hand side of this expression, we have the sum of two terms raised to the power of three.
00:03:08.560 --> 00:03:10.240
This is a binomial.
00:03:10.440 --> 00:03:17.920
So we can expand the right-hand side of this expression by using the binomial theorem.
00:03:18.720 --> 00:03:38.480
Remember, this tells us for any positive integer value of π, π plus π all raised to the πth power is equal to the sum from π equals zero to π of π choose π times π to the power of π multiplied by π to the power of π minus π.
00:03:39.560 --> 00:03:45.280
So, by using the binomial formula, we can expand the right-hand side of our equation.
00:03:46.360 --> 00:04:08.200
We get three choose zero times π§ cubed plus three choose ~~zero~~ [one] multiplied by π§ squared times one over π§ plus three choose two times π§ multiplied by one over π§ all squared plus three choose three times one over π§ all cubed.
00:04:09.440 --> 00:04:12.800
And we can simplify the right-hand side of this expression.
00:04:13.240 --> 00:04:15.640
Weβll do this term by term.
00:04:16.440 --> 00:04:21.000
In our first term, three choose zero is equal to one.
00:04:21.880 --> 00:04:25.560
So our first term simplifies to give us π§ cubed.
00:04:25.760 --> 00:04:38.800
In our second term, three choose one is equal to three and π§ squared times one over π§ is π§ squared over π§, which simplifies to give us π§.
00:04:38.800 --> 00:04:44.080
So our second term simplifies to give us three π§.
00:04:44.920 --> 00:04:58.840
In our third term, three choose two is equal to three and π§ times one over π§ all squared is π§ divided by π§ squared, which simplifies to give us one over π§.
00:04:59.640 --> 00:05:03.560
So our third term simplifies to give us three over π§.
00:05:04.520 --> 00:05:15.160
And in our fourth and final term, three choose three is equal to one and one over π§ all cubed is one over π§ cubed.
00:05:16.000 --> 00:05:19.880
So our fourth term is just one over π§ cubed.
00:05:21.400 --> 00:05:32.880
So, so far, weβve shown that eight cos cubed of π is equal to π§ cubed plus three π§ plus three over π§ plus one over π§ cubed.
00:05:34.000 --> 00:05:45.640
But this isnβt enough because, remember, the question wants us to find an expression for cos cubed of π only in terms of cosines of multiples of π.
00:05:46.480 --> 00:05:49.640
And to do this, weβre going to need to notice something.
00:05:50.560 --> 00:05:55.040
On the right-hand side of our expression, we can actually simplify.
00:05:55.800 --> 00:06:05.880
For example, on the right-hand side of our expression, we have π§ cubed plus one over π§, which we can simplify by using De Moivreβs theorem.
00:06:06.560 --> 00:06:12.000
π§ to the πth power plus one over π§ to the πth power is two cos of ππ.
00:06:13.200 --> 00:06:18.680
So π§ cubed plus one over π§ cubed is two cos of three π.
00:06:19.000 --> 00:06:27.480
So weβll pair these two terms up on the right-hand side of our expression.
00:06:28.320 --> 00:06:33.840
And we will be able to see we can also do this with three π§ plus three over π§.
00:06:34.680 --> 00:06:40.240
First, we need to take out the shared factor of three from both of these terms.
00:06:41.160 --> 00:06:45.760
This leaves us with π§ plus one over π§ inside of our parentheses.
00:06:46.360 --> 00:06:55.160
And π§ plus one over π§ is this exact same result with π set to be one.
00:06:56.200 --> 00:07:09.360
By De Moivreβs theorem, π§ plus one over π§ is two cos of π and π§ cubed plus one over π§ is two cos three π.
00:07:10.360 --> 00:07:14.520
So we can substitute both of these into our expression.
00:07:15.480 --> 00:07:19.640
And remember, we need to multiply two cos of π by three.
00:07:20.280 --> 00:07:25.280
This gives us two cos of three π plus six cos π.
00:07:26.160 --> 00:07:30.920
And remember, this is all equal to eight cos cubed of π.
00:07:32.280 --> 00:07:42.240
Now, we can find an expression for cos cubed of π in terms of cosines of multiples of π by dividing both sides of our equation through by eight.
00:07:43.160 --> 00:07:47.600
Weβll divide each term separately on the right-hand side by eight.
00:07:48.560 --> 00:07:58.680
This gives us cos cubed of π is equal to two cos of three π all over eight plus six cos of π all over eight.
00:07:59.520 --> 00:08:01.440
And we can simplify the right-hand side.
00:08:02.200 --> 00:08:15.160
We can cancel the shared factor of two in the numerator and denominator of both terms, giving us cos of three π all over four plus three cos of π all over four.
00:08:16.200 --> 00:08:19.680
And weβll simplify this by taking out the shared factor of one-quarter.
00:08:20.440 --> 00:08:26.120
This gives us one-quarter multiplied by cos of three π plus three cos of π.
00:08:27.520 --> 00:08:32.680
And the last piece of simplification weβll do is reorder the two terms inside of our parentheses.
00:08:33.560 --> 00:08:42.000
And this gives us our final answer of one-quarter multiplied by three cos π plus cos of three π.
00:08:43.040 --> 00:08:57.200
Therefore, by using De Moivreβs theorem and several results we get from De Moivreβs theorem, we were able to find an expression for cos cubed of π in terms of cosines of multiples of π.
00:08:58.000 --> 00:09:08.000
We were able to show cos cubed of π is equal to one-quarter multiplied by three cos of π plus cos of three π.